2019
DOI: 10.15587/1729-4061.2019.171063
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of consumer properties of nutria velour hydrophobicized with alkenmalein-acrylsyntane composition

Abstract: Досліджено комплекс споживних властивостей гідрофобізованого хутрового велюру нутрії з використанням алкенмалеїно-акрилсинтанової композиції. Склад цієї композиції включає алкенмалеїновий полімер, поліакриловий полімер і синтанний дубитель. Процес наповнювання-гідрофобізаії хутрового велюру нутрії проводиться за рН робочого розчину 6,8-7,0, температури 40-43 °С та тривалості три години і закінчується за рН 3,8-4,0. Гідрофобізований хутровий велюр нутрії отримували з неякісної за волосяним покривом сировини, не… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The generalized desirability criterion is a weighted product of partial desirability criteria, which, in their turn, are normalized estimates of the state of the studied system, presented in fractions of a scale unit (from 0.0 to 1.0) and obtained from target functions by encoding these functions based on a special "scale of preferences". Harrington's desirability function was used in this study, which showed sufficient efficiency compared to other desirability functions [25]. The effectiveness of the desirability-based approach compared to other multi-purpose optimization strategies has been confirmed by numerous studies [26][27][28][29].…”
Section: Multi-objective Optimization Of Liming Technology Using Harr...mentioning
confidence: 81%
“…The generalized desirability criterion is a weighted product of partial desirability criteria, which, in their turn, are normalized estimates of the state of the studied system, presented in fractions of a scale unit (from 0.0 to 1.0) and obtained from target functions by encoding these functions based on a special "scale of preferences". Harrington's desirability function was used in this study, which showed sufficient efficiency compared to other desirability functions [25]. The effectiveness of the desirability-based approach compared to other multi-purpose optimization strategies has been confirmed by numerous studies [26][27][28][29].…”
Section: Multi-objective Optimization Of Liming Technology Using Harr...mentioning
confidence: 81%
“…The amount of experimental data can be substantially reduced by using the McLean-Anderson algorithm, which assumes that all possible combinations (more than 10 9 ) of N theoretical points of candidates selected by the McLean-Anderson algorithm [16] are provided, on condition that 1 | |min. In order to establish the coefficients of model (3), we select the minimum number of experimental points n = 10.…”
Section: Obtaining a Mathematical Model "The Structure Of The Fillingmentioning
confidence: 99%
“…The use of raw materials of nutria skin for velour resistant to the environment requires a significant modification of the porous structure of the skin tissue [1]. For this purpose it is necessary to carry out the processes of filling-hydrophobization of fur semi-finished products using the methods of mathematical modeling and multifactor optimization.…”
Section: Introductionmentioning
confidence: 99%